Grounding and Logical Basing Permissions (Diametros, 2016)
The relation between logic and rationality has recently re-emerged as an important topic of discussion. Following the ideas of Broome [1999] and MacFarlane [2004], the debate focused on providing rational requirements, which work as bridges between logic and epistemic norms. However, as Broome [2014] and Way [2011] observed, the usual requirements cannot capture some important aspects of rationality, such as how one can rationally believe something on the basis of believing something else. Broome [2014] proposed a few additional principles (“basing permissions”) for this purpose. In this paper I develop a more systematic family of basing permissions using the recent notion of grounding (Fine [2012], Correia [2014]). In particular, I claim that if Γ (logically) grounds A, and you believe Γ, then rationality permits you to believe A on the basis of believing Γ.